2020
DOI: 10.3390/jpm10030109
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 Expression Has Regulatory Properties and Prognostic Value in Lung Cancer

Abstract: Lung cancer remains the most dangerous type of cancer despite recent progress in therapeutic modalities. Development of prognostic markers and therapeutic targets is necessary to enhance lung cancer patient survival. Sestrin family genes (Sestrin1, Sestrin2, and Sestrin3) are involved in protecting cells from stress. In particular, Sestrin2, which mainly protects cells from oxidative stress and acts as a leucine sensor protein in mammalian target of rapamycin (mTOR) signaling, is thought to affect various canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Sesn2-deficient mouse embryonic fibroblast (MEF) cells were significantly more susceptible to oncogenic stresses (Budanov and Karin, 2008). Sesn2 inhibition promotes A549, human a non-small cell lung carcinoma, cell growth (Sablina et al, 2005), and its expression level is negatively correlated with the lung cancer survival rate (Chae et al, 2020). Sesn3 induces apoptosis of human non-small cell lung cancer (NSCLC) cells in dietary compound cucurbitacin B treatment (Khan et al, 2017).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Sesn2-deficient mouse embryonic fibroblast (MEF) cells were significantly more susceptible to oncogenic stresses (Budanov and Karin, 2008). Sesn2 inhibition promotes A549, human a non-small cell lung carcinoma, cell growth (Sablina et al, 2005), and its expression level is negatively correlated with the lung cancer survival rate (Chae et al, 2020). Sesn3 induces apoptosis of human non-small cell lung cancer (NSCLC) cells in dietary compound cucurbitacin B treatment (Khan et al, 2017).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Interestingly, in contrast to this study, Chae et al demonstrated that the expression of sestrin 2 in lung cancer was higher than in normal lung tissue by using the Oncomine and Human Protein Atlas databases. Furthermore, these authors showed that overexpressed sestrin 2 was a marker for poor prognosis in lung cancer by analyzing the PrognoScan database and Kaplan–Meier Plotter [ 44 ]. Additionally, by analyzing data from the Gene Expression Omnibus and Cancer Genome Atlas analysis, Lin et al revealed that the survival time for lung cancer patients with lower sestrin 2 expression was significantly prolonged [ 45 ].…”
Section: The Alteration Of Sestrin 2 Gene Expression In Various Cancersmentioning
confidence: 99%
“…Sestrin 2 also has a potentially oncogenic function in lung cancer. Knockdown of sestrin 2 with shRNA inhibited proliferation, migration, and sphere formation in A549 cells [ 44 ]. In pancreatic cancer, overexpression of sestrin 2 promoted PANC-1 cells proliferation and increased glycolysis, and mTOR inhibitors suppressed these effects in vitro.…”
Section: Promotive Effects Of Sestrin 2 In Cancermentioning
confidence: 99%
“…Among sestrin family, Sestrin2 has shown regulating activities in some cancers [14]. Knocking down Sestrin2 in non-small cell lung cancer cells resulted in reduced lung cancer progression [15]. Down-regulation of Sestrin2 promoted cell proliferation, migration, and ROS production in endometrial cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%